Public Relations Principles for the Digital Communication in a Local Crisis (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
In dealing with the crisis, all institutions must react and urgently solve the problem, but a special challenge is to communicate with key publics, especially those publics that have suffered damage., What is imperative for public relations is fast and two-way communication. That is why digital platforms are indispensable in crisis communication because they enable almost simultaneous reaction and enable institutions to communicate directly with the affected public, without the mediation of information media. This paper aims to analyse the crisis communication of the City of Slavonski Brod through its official website and Facebook page during water pollution in March and April 2018. The analysis was performed by methods of qualitative content analysis and a case study analysis. During the environmental incident, the City of Slavonski Brod did not communicate following the PR principles of crisis communication nor took advantage of digital communication.